PENGETAHUAN LOKAL TUMBUHAN OBAT MASYARAKAT DESA DOMPO-DOMPO JAYA, PULAU WAWONII - SULAWESI TENGGARA - Royyani, Mohammad Fathi; Rahayu, Mulyati (Jurnal Teknologi Lingkungan, 2010)
The ethnobotanical study of plants usage of people in the Wawonii island was conducted in April until May 2006. The local knowledge of medicinal plants in Wawonii island is a result from interaction people of Wawonii island. Environment, another ethnics and globalization, it is as cultured processes. Data were collected on the uses of plants, and more than 62 species of plants were recorded in local names. The data are discussed in the contect of Wawonii island culture, tradition, and way of life. Furthurmore, plants used also show the nearness of emotional relationship between human and environment.Key words: Indigenous knowledge, medicinal plants, Wawonii ethnic, SoutheastSulawesi